A Retrospective, Longitudinal Registry Study on the Long-Term Durability of Ivacaftor Treatment in People with Cystic Fibrosis - Christian Merlo; Teja Thorat; Lisa J. McGarry; Christina V. Scirica; Maral DerSarkissian; Catherine Nguyen; Yuqian M. Gu; Aruna Muthukumar; Joe Healy; Jaime L. Rubin; M. Alan Brookhart (Pulmonary Therapy)
Abstract Introduction Ivacaftor (IVA) has been shown to change the trajectory of cystic fibrosis (CF) disease progression by slowing the rate of lung function decline in clinical studies. Long-term real-world data help to confirm the durability of this response. Methods This non-interventional, longitudinal study used data from the US CF Foundation Patient Registry to describe the annualized rate of change in lung function in people with CF receiving IVA. The IVA-treated cohort included people with CF aged ≥ 6 years who had ≥ 1 CF transmembrane conductance regulator (CFTR)–gating mutation and initiated IVA between 31 January 2012 and 31 December 2018. An age-matched comparator cohort included people with CF heterozygous for the F508del-CFTR mutation and a minimal function mutation (R117H excluded) and had not received CFTR modulator therapy. Baseline characteristics were balanced using standardized mortality ratio (SMR) weights computed from estimated propensity scores. The annualized rate of change in percent predicted forced expiratory volume in 1 s (ppFEV1) was estimated over 5 years and used to calculate the relative annualized rate of change in lung function in the IVA-treated versus comparator cohorts. Results In the 5-year follow-up period, 548 people were in the IVA-treated and 541 in the comparator cohorts after SMR weighting. The annualized rate of change in ppFEV1 over 5 years was −1.23 (95% CI −1.45, −1.03) and −2.03 (−2.16, −1.90) percentage points in the IVA-treated and comparator cohorts, respectively. There was a 39% reduction (95% CI: 28, 50) in the rate of lung function decline in the IVA-treated versus comparator cohort over 5 years. Findings were generally consistent with those of shorter follow-up periods. Conclusion IVA showed a durable clinical benefit by slowing the rate of lung function decline over 5 years. Results support a sustained and consistent impact of IVA on lung function trajectory in people with CF. Word count: 300 (limit: 300 words).